Three-dimensional position estimation method via AM pulse light modulation and an application to control multiple UAVs. (2nd October 2018) - Sukisaki, Seita; Shimomura, Ryo; Nobuhara, Hajime
ABSTRACT: In this study, a three-dimensional position estimation is proposed to estimate self-position via amplitude-modulated pulse infrared light to solve the problem of position estimation from an existing device used in the cooperation of unmanned air vehicles (UAVs) that can be used in various environments. The proposed method estimates self-position as the distance between the receiver and the transmitter and the angle of direction by attenuation of amplitude-modulated pulse infrared light. By attaching a transmitter to a leader UAV and a receiver to follower UAVs, the cooperation flight can be achieved. The following three experiments are conducted: (1) evaluation of the accuracy of self-position estimation, (2) implementation of the proposed method on an UAV, and (3) evaluation of the robustness of the proposed method in an outdoor environment. The findings confirm the effectiveness of the proposed method. The proposed approach allows estimation of position with high speed, precision in various environments, and low-cost devices. GRAPHICAL ABSTRACT: